2021
DOI: 10.3390/math9040354
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Hopf Bifurcation in a Generalized Genesio Differential Equation

Abstract: The purpose of the present paper is to study the presence of bifurcations of zero-Hopf type at a generalized Genesio differential equation. More precisely, by transforming such differential equation in a first-order differential system in the three-dimensional space R3, we are able to prove the existence of a zero-Hopf bifurcation from which periodic trajectories appear close to the equilibrium point located at the origin when the parameters a and c are zero and b is positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Braun and Mereu [2] obtained a zero-Hopf bifurcation in a chaotic jerk system. Diab et al [6] investigated zero-Hopf bifurcations of the generalized Genesio differential equation. In their work, they characterized the existence of a zero-Hopf equilibrium point and showed that at most 6 periodic solutions bifurcate from the origin of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Braun and Mereu [2] obtained a zero-Hopf bifurcation in a chaotic jerk system. Diab et al [6] investigated zero-Hopf bifurcations of the generalized Genesio differential equation. In their work, they characterized the existence of a zero-Hopf equilibrium point and showed that at most 6 periodic solutions bifurcate from the origin of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, Appendix: Averaging theory of first order for limit cycles Now we'll go through the basic averaging theory for Lipschitz differential systems which we'll need to prove result of isolated limit cycle bifurcate from zero-Hopf point. The following theorem offers a first-order of the averaging theory for differential system which founded in [25], [26] and used in [12], [27], and [28]. For more information and the proof see previous references.…”
mentioning
confidence: 99%